How a distance of 10 feet can be fatal - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
In September 2008 the Little General Store in West Virginia exploded. The findings of investigators revealed a number of areas where poor procedures and lax managing of resources led to the tragedy. This case asks students to think about what steps could be put in place to ensure a similar disaster does not reoccur.